PENANGANAN LIMBAH MEDIS DAN PERILAKU PETUGAS CLEANING SERVICE DI RSUD Dr. SOETOMO SURABAYA TAHUN 2016 - Risca Anesea; Erna Triastuti; Ferry Kriswandana (Poltekkes Kemenkes Surabaya, 2016)
Health workers who handle medical waste are at risk of the diseases faced because of germs from the skin infections, anthrax, meningitis, dengue, hepatitis A, Hepatitis B and C. The bacteria present in the blood are transmitted through blood. The highest risk of being infected by these diseases is when impaled by sharp or pointed object of the waste because it can damage the skin. The purpose of this study was to determine the behavior of CS officers (Cleaning Service) and the handling of medical waste in Dr. Soetomo hospital. This is a descriptive research with cross sectional approach. The collection of data was carried out through observation and interviews. The sample was 75 CS officers. Data were analyzed descriptively with table analysis.The results showed that Cleaning Services’ level of knowledge at Dr. Soetomo Hospital on handling medical waste with